Monopoly Media “Unggah-Ungguh Basa” on Speaking Skills of “Bahasa Jawa Ragam Krama” in Junior High Schools - Setiawan, Bambang; Insani, Nur Hanifah (Journal of Education Reseach and Evaluation, 2025)
The process of learning Javanese language on the material of politeness for speaking skills of Javanese krama variety still uses conventional media models (speech/lecture) through the use of textbooks and blackboards without any renewal of the learning model. This has an impact on the low speaking skills of the Javanese krama variety in students. The study aims to test the effectiveness of learning media by implementing the media of politeness monopoly for grade VIII junior high school students. The type of research applied in this study is Quasi-Experimental Design through the Nonequivalent Control Group Design. The research sample amounted to 62 students, with 30 students (experimental) and 32 students (control), using random sampling techniques. Data collection techniques in this study include interviews with class teachers, observation, documentation, and written tests. Data collection instruments use questionnaire sheets and test questions. This study applies analysis techniques through the Independent sample T-test and N-Gain tests. The results of this study showed that there was a difference in the average between the learning outcomes of speaking skills on the material of politeness in the experimental class and the control class. Learning models by applying creative innovative media using language monopoly media is stated to be effective significantly by 85% in the experimental class, while 37% in the control class to improve Javanese language speaking skills in the krama variety. It is concluded that language monopoly media can help students in learning the Javanese language in the krama variety, so that they can improve their language speaking skills in the krama variety. The implication of the research is that language monopoly media can be used in learning.